Peseptual Motor Disabilitas Kecerdasan Pada Keterampilan Activity Of Daily Living - Sulistyaningrum, Noorita Dwi (PEMBELAJAR: Jurnal Ilmu Pendidikan, Keguruan, dan Pembelajaran, 2018)
This study aims to determine and describe the power of the perceptual motor in students with intellectual disabilities in skills activity of daily living (ADL). Research methods used is descriptive study with quantitative approach. The data in this study were collected through 3 (three) data collection techniques namely test, observation, and interview. Participants in this study consisted of 2 students with grade 2 SDLB intellectual disabilities with an age range of 8-12 years. The results obtained from this study indicate that perceptual motors in students with intellectual disabilities for activity of daily living (ADL) skills are still incomplete, requiring practice for ability perceptual motor. This is evidenced, from the results of perceptual motor for self-construction skills wearing buttoned clothes of 4.5 (perceptual motor is not yet complete), wearing socks of 5 (perceptual motor is complete) and wearing shoes of 4 (perceptual motor is not yet complete). Based on the results of the study, the overall score of 4.5 is categorized as having ability perceptual motor is not yet complete, thus requiring various exercises to have the power perceptual motor